Groundstroke Training Equipment Innovation for Beginner Tennis Players - Fauzan, Lazuardy Akbar; Mulhim, Muhammad; Dirgantoro, Edwin Wahyu; Amirudin, Akhmad; Perdinanto, Perdinanto (Indonesian Journal of Physical Education and Sport Science, 2024)
Study Purpose. Forehand and backhand groundstrokes are the basic strokes in tennis that need to be mastered. The training process needs to be supported by the availability of training equipment facilities so that it can help athletes and coaches to achieve training goals. The aim of this research is to produce an innovative tennis groundstroke training tool for beginner players. The novelty in this research is that it produces an innovative tennis groundstroke training tool that can be used for forehand and backhand training. Materials and Methods. This research is research and development research. The research design in the research uses the ADDIE development model. The sample was 19 novice tennis players from Sabumi Tennis Club Banjarbaru. Result. 1) The development of training equipment has gone through the stage of identifying the needs of athletes and coaches with the results in the very needed category, 2) The results of validation testing obtained an expert validity score of 90.47% in the very good category, 3) The small trial stage obtained a score of 85.4% in very good category. The large trial stage obtained a score of 89.56% in the very good category. 4) The response of the trainer who carried out the assessment concluded that the training tools were very suitable and useful to be applied in the training process. Conclusion. 1) Researchers produced a training tool called "Double Drop ball". 2) This tool can be used to practice forehand and backhand groundstrokes for beginner players. 3) The advantage of this tool is that it can be used for forehand and backhand groundstroke training 4) The disadvantage of this tool is that it is limited to groundstroke practice 5) Recommendations for researchers can develop a multifunctional tool for practicing other basic techniques.